A review for future research and practice in using computer assisted instruction on vocabulary learning among children with autism spectrum disorder - Dzulkifli, Mariam Adawiah; Abdul Wahdi, Elok Vradizza Feni; Abdul Rahman, Abdul Wahab (The Institute of Electrical and Electronics Engineers, Inc., 2016)
A lack of educational strategies may hinder students from benefiting the most from their education. The existing public or government schools do not adequately accommodate children with special needs in terms of providing them with good syllabuses as well interventions. Instead, various forms of pervasive developmental disorders are frequently placed in special education classes without an accurate diagnosis. This is something that needs to be rectified because every disability requires different needs and attention. In children with special needs such as children with Autism Spectrum Disorder (ASD), it warrants diverse teaching methods to be used. While the use of computer assisted instructions (CAIs) in the West has been found to be effective for children with ASD, research regarding the applicability of CAIs to cater for the learning process of children with special needs in the Malaysian context is still lacking. The present paper reviews previous studies that have employed CAIs to enhance language development of children with ASD. Following this, it recommends future research that incorporates the use of CAI to improve vocabulary learning of children with ASD who are non-native English speakers.